Animal and Human Digestive System Material of the Fifth Grade Elementary School in the form of Pop-Up Book Media - Noviyanti, Dewa Ayu Putu Mega; Margunayasa, I Gede (Journal of Education Technology, 2020)
The limited relevant learning resources and the lack of development on natural science content on the topic of the animals and human digestive system were the reasons for this research. This research aimed at developing Pop-Up book media on the topic of animal and human digestive system in which the validity had been tested. This research was developmental research by using some steps, such as analyze, design, development, implementation, and evaluation models. However, the implementation steps and the evaluation steps were not conducted due to time limitations. The data collection method used in this research was a questionnaire method. The subject of this research was a learning media in the form of a Pop-Up book on the topic of animal and human digestive system on the fifth-grade elementary school students and the object of this research was the validity on learning media for Pop-Up book media. The instrument used in this developmental research was the rating scale. From the results of the assessment by four experts, an average score of 4.79 was obtained into very good qualification. Based on the results of the assessment, it could be concluded that the Pop-Up book media on the topic of animal and human digestive system was valid with a very good qualification. The existence of a Pop-Up book media was useful to assist the teachers’ tasks in implementing learning specifically in developing natural science materials on the topic of animal and human digestive system.